Caste discrimination and exclusion in Indian universities : a critical reflection - Sukumar, N. (Sociologist) (London ; New York, NY : Routledge, Taylor & Francis Group, 2023)
"This book studies the exclusion and discrimination that is meted out to Scheduled Caste (SC) students in the Indian Higher Education system, and the psycho-social consequences of such practices. It foregrounds the conceptual debates around caste, exclusion, and reservations in Indian academia, discussing the social dominance and the roots of prejudices in the university spaces. The volume reflects upon the fragile social world in which students from the margins struggle for survival in the academic space. It reveals that these students navigate the various facets of academia like classrooms, pedagogy, scholarships, hostels, peer groups, and teachers, only to find the academic space a dystopian universe. The book also sheds light on suicide cases committed by the marginalized groups as a testimony of protest. Based on in-depth ethnographic research, this book will be of interest to teachers, students, and researchers of education, sociology, political science, psychology, and exclusion studies. It will also be useful for policymakers, social activists, NGOs, research centers, and those working in higher education, reservations, public policy, caste, and exclusion studies"--
Includes bibliographical references and index.
Keywords: Caste-based discrimination -- India; Marginality, Social -- India; Universities and colleges -- India -- Admission; India -- Scheduled castes